A randomized controlled trial of two dialysate sodium concentrations in hospitalized hemodialysis patients. Issue 7 (18th November 2021) - Causland, Finnian R Mc; Ravi, Katherine Scovner; Curtis, Katherine A; Kibbelaar, Zoé A; Short, Samuel A P; Singh, Anika T; Correa, Simon; Waikar, Sushrut S
ABSTRACT: Background: Several large dialysis organizations have lowered the dialysate sodium concentration (DNa) in an effort to ameliorate hypervolemia. The implications of lower DNa on intra-dialytic hypotension (IDH) during hospitalizations of hemodialysis (HD) patients is unclear. Methods: In this double-blind, single center, randomized controlled trial (RCT), hospitalized maintenance HD patients were randomized to receive higher (142 mmol/L) or lower (138 mmol/L) DNa for up to six sessions. Blood pressure (BP) was measured in a standardized fashion pre-HD, post-HD and every 15 min during HD. The endpoints were: (i) the average decline in systolic BP (pre-HD minus lowest intra-HD, primary endpoint) and (ii) the proportion of total sessions complicated by IDH (drop of ≥20 mmHg from the pre-HD systolic BP, secondary endpoint). Results: A total of 139 patients completed the trial, contributing 311 study visits. There were no significant differences in the average systolic blood pressure (SBP) decline between the higher and lower DNa groups (23 ± 16 versus 26 ± 16 mmHg; P = 0.57). The proportion of total sessions complicated by IDH was similar in the higher DNa group, compared with the lower DNa group [54% versus 59%; odds ratio 0.72; 95% confidence interval (95% CI) 0.36–1.44; P = 0.35]. In post hoc analyses adjusting for imbalances in baseline characteristics, higher DNa was associated with 8 mmHg (95% CI 2–13 mmHg) less decline in SBP, compared with lower DNa. Patient symptoms and adverse events were similar between the groups. Conclusions: In this RCT for hospitalized maintenance of HD patients, we found no difference in the absolute SBP decline between those who received higher versus lower DNa in intention-to-treat analyses. Post hoc adjusted analyses suggested a lower risk of IDH with higher DNa; thus, larger, multi-center studies to confirm these findings are warranted. Graphical Abstract: